Quality of Life in a mixed ethnic population after myocardial infarction - Webster, Rosemary A.; Thompson, David R.; Larkin, Derek; Mayou, Richard A.; Martin, Colin R. (European Journal for Person Centered Healthcare, 2017)
Background: Although South Asian people are a significant ethnic group at increased risk of coronary heart disease and high mortality rates and experience greater delays with respect to diagnosis, referral and treatment, comparatively little is known about their quality of life during recovery from a myocardial infarction. Objectives: We sought to determine and compare the impact of ethnicity on quality of life after myocardial infarction (MI) in a mixed ethnic population (South Asian and white people) in the UK. Methods: A 2x2 mixed-group design with repeated measures on the second factor. The independent variables were ethnic group (white/South Asian) and time since MI (2 weeks/3 months). The dependent variables were the subscale scores on the Short-Form 36-item health survey (SF-36) and the Hospital Anxiety and Depression Scale (HADS). Results: At 2 weeks, significant differences were observed between groups on 5 of the 8 SF-36 subscale domain scores, with the white group reporting higher quality of life. Significant improvement in reported quality of life occurred in both groups over time on all domains of the SF-36, except bodily pain. There was a significantly greater improvement in favour of the white group for the role-physical domain. There was no significant difference between groups in terms of anxiety or depression at 2 weeks. Both groups showed a significant reduction in anxiety and depression by 3 months, but the degree of reduction was not significantly different between them. At 3 months, there was no significant difference between groups in terms of anxiety scores, but the South Asian group scored significantly higher on the depression scale. Conclusions: South Asian people have significantly poorer quality of life than white people after MI. While both groups showed improvement over time, South Asian people reported significantly less improvement in physical role function and were more depressed at 3 months. Identifying the factors accounting for such differences is important to develop models of care for delivering the most effective and culturally-sensitive interventions to this group.
Keywords: Quality of Life; Anxiety; Depression; South Asian; Myocardial infarction